2023
DOI: 10.3934/microbiol.2023005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance genes of <i>Escherichia coli</i>, a bacterium of “One Health” importance in South Africa: Systematic review and meta-analysis

Abstract: <abstract> <p>This is a systematic review and meta-analysis that evaluated the prevalence of <italic>Escherichia coli</italic> antibiotic-resistant genes (ARGs) in animals, humans, and the environment in South Africa. This study followed Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines to search and use literature published between 1 January 2000 to 12 December 2021, on the prevalence of South African <italic>E. coli</italic> isolates' A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Balakrishnan et al , 2016 [ 30 ] isolated fluoroquinolones resistant E. coli isolates of animal origin from Puducherry. In contrast, Ramatla et al, 2022 [ 55 ] found a higher percentage of qnrA and tet gene resistance in rodents in South Africa. These quinolones are being used to treat human Salmonellosis for over 4 decades.…”
Section: Discussionmentioning
confidence: 93%
“…Balakrishnan et al , 2016 [ 30 ] isolated fluoroquinolones resistant E. coli isolates of animal origin from Puducherry. In contrast, Ramatla et al, 2022 [ 55 ] found a higher percentage of qnrA and tet gene resistance in rodents in South Africa. These quinolones are being used to treat human Salmonellosis for over 4 decades.…”
Section: Discussionmentioning
confidence: 93%
“…A growing number of studies have reported that any environment has the potential to be a host for ARGs, with human, animal, and environmental components interacting and contributing directly or indirectly to the spread of ARGs ( Dai et al, 2023 ; Ramatla et al, 2023 ). Therefore, ARGs are considered to be a new environmental pollutant ( Zhu et al, 2017 , 2018 ; Zhang et al, 2020 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…APEC strains cause many systemic and local infections in poultry, including ducks, turkeys, chickens, and other avian spp. ( Dho-Mouline and Fairbrother, 1999 ; Ramatla et al, 2023 ).…”
Section: Introductionmentioning
confidence: 98%